REPRESENTASI BODY POSITIVITY DALAM KONTEN INSTAGRAM INFLUENCER TARA BASRO - Dinda Ayu Permatasari; Nuriyatul Lailiyah (Interaksi Online, 2026)
The dominance of beauty standards on social media, which portray slim bodies, fair skin, and flawless appearances as the ideal for women, remains a serious issue in Indonesia. This study aims to describe the denotative and connotative meanings of body positivity and to analyze biases in the representation of women’s bodies in Tara Basro’s content. Using a descriptive qualitative approach with a critical paradigm and Roland Barthes’s semiotic method, the research object consists of Tara Basro’s Instagram posts containing messages of body positivity. The analysis was conducted by examining the denotative, connotative, and mythical meanings of the visual and textual elements in the posts. The results indicate that body positivity is represented through the natural appearance of women’s bodies, dark brown skin tones, skin textures, body contours, and narratives of self-acceptance. These representations signify courage, authenticity, and resistance to dominant beauty standards. However, this study also found an ambivalence because these representations still contain aesthetic biases, commercial biases, and social class biases. This study concludes that the representation of body positivity in Tara Basro’s Instagram content serves as a space for a battle of meanings between resistance to beauty standards and negotiation with the logic of social media.